2017
DOI: 10.1590/1678-69712017/administracao.v18n4p11-38
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty, Flexibility and Operational Performance of Companies: Modelling From the Perspective of Managers

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. ADILSON ADERITO SILVAUniversidade Presbiteriana Mackenzie (UPM), São Paulo -SP, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…From the perspective of Venkatraman and Ramanujam (1986), both financial performance and operational performance are the main determinants of the effectiveness of a company. While financial performance involves indicators such as sales growth, profitability and earnings per share, among others, operational performance relates to measures such as market share, the introduction of new products, product quality and value added in manufacturing, among others (Silva and Ferreira, 2017).…”
Section: Performancementioning
confidence: 99%
“…From the perspective of Venkatraman and Ramanujam (1986), both financial performance and operational performance are the main determinants of the effectiveness of a company. While financial performance involves indicators such as sales growth, profitability and earnings per share, among others, operational performance relates to measures such as market share, the introduction of new products, product quality and value added in manufacturing, among others (Silva and Ferreira, 2017).…”
Section: Performancementioning
confidence: 99%
“…Uncertainty is seen as the scenario where predicting outcomes are incredibly tough due to the complex dynamic nature of the business environment (Silva & Ferreira, 2017).…”
Section: Uncertainties/disruptions In the Wake Of Covid 19mentioning
confidence: 99%
“…Using a subjective measurement of uncertainty, defined as a reflective multidimensional concept formed from the three types of uncertainty adopted from Milliken (1987), Silva and Ferreira (2017) reported that managers in diverse operational management firms had a moderate level of effect and SU and that this perception was connected to their firms' flexibility and performance. In contrast to the earlier findings on the connections between EU and RU, the authors found that favorable levels of EU observed in managers' perceptions reduced the difficulties they faced in interpreting and selecting alternative responses to environmental changes (Silva & Ferreira, 2017). In exploring the relationships between the three types of uncertainty, Sund (2008) Perceived uncertainty about the effects of uncertainty on the organization has been found to have a negative influence on decisionmakers' tendency to engage in action in an entrepreneurial context (McKelvie et al, 2011).…”
Section: Contextual and Theoretical Underpinningsmentioning
confidence: 99%
“…Knowledge workers must analyze their external domains for emerging situations and challenges, particularly in uncertain times (Spender & Strong, 2014), because the “COVID‐19 pandemic is maturing, but uncertainties continue to multiply for individuals and for policy makers” (Rutter et al, 2020, p. 1). Thus, the focus of uncertainty‐related studies should not be limited to managers (i.e., Hsu & Wang, 2008; Silva & Ferreira, 2017). Therefore, this study included all the primary employees of an institution of higher education—specifically, academics at a university in the Philippines—as participants in its research.…”
Section: Introductionmentioning
confidence: 99%